Authenticity in marketing: A response to consumer resistance? - Christine Marks; Melani Prinsloo (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2015)
Prior research points out the emerging phenomenon of consumer resistance in terms of resistance towards the marketing discipline. At the same time, extant literature suggests the increasing importance of authenticity in marketing.This study investigates the research question whether and by which means authenticity in marketing can be a response to consumer resistance. The authors conducted qualitative research within which one part of the interviews was conducted with marketing-resistant participants, another one with non-resistant respondents. This permitted to elaborate on divergences between the two groups concerning the evaluation of authenticity.The results illustrate that resistant consumers showed a greater sensitivity for authenticity and clear preferences for authentic brands compared to a more indifferent assessment of the comparison group. Resistant consumers were more likely to identify themselves with the presented authentic brands and appreciated their benefits such as autonomy, closeness, quality assurance, individuality and economic rebellion that directly contrast with the elaborated points of criticism about marketing. This suggests that, in order to regain consumers that are critical towards the marketing discipline, the elaborated authenticity facets could be applied to brands as an "antidote".
Keywords: M00; M30; M31; 650; authenticity; authentic marketing; consumer resistance; marketing skepticism